Dual Trajectories of Depression/Anxiety Symptoms and Alcohol Use, and their Implications for Violence Outcomes Among Drug-Using Urban Youth. (26th May 2018) - Goldstick, Jason E; Bohnert, Kipling M; Davis, Alan K; Bonar, Erin E; Carter, Patrick M; Walton, Maureen A; Cunningham, Rebecca M
Abstract : There were five characteristic dual trajectories of alcohol use and depression/anxiety symptoms. Community violence exposure was highest among individuals with high-depression/anxiety symptom trajectories. Individuals with concurrently high-alcohol use and depression/anxiety symptom trajectories reported that the most delinquent peer affiliations, and had the highest rates of severe violence over time. Abstract: Aim: To examine dual trajectories of anxiety/depression symptoms and alcohol use among drug-using youth seeking care from an urban emergency department (ED), their baseline correlates and co-occurring trajectories of severe violence. Short summary: There were five characteristic dual trajectories of alcohol use and depression/anxiety symptoms. Community violence exposure was highest among individuals with high-depression/anxiety symptom trajectories. Individuals with concurrently high-alcohol use and depression/anxiety symptom trajectories reported that the most delinquent peer affiliations, and had the highest rates of severe violence over time. Methods: We analyzed data from 599 drug-using (primarily marijuana) youth ages 14–24 (349 assault-injured) recruited from December 2009 to September 2011 into a 24-month longitudinal study at a Level-1 ED in Flint, Michigan. Youth self-reported substance use, depression and anxiety symptoms, peer/parental behaviors, and severe violence involvement at baseline and four biannual follow-up assessments. Bivariate latent trajectory models identified homogeneous groups with similar trajectories on alcohol use and anxiety/depression symptoms; we compared baseline characteristics of each trajectory group and concurrent trajectories of severe violence (victimization and aggression). Results: Our model identified five trajectory groups: Low drinking/No symptoms (LN; 10.4%; n = 62), No drinking/Moderate symptoms (NM; 15.7%; n = 94), Low drinking/Moderate symptoms (LM; 30.2%; n = 181), Low drinking/High symptoms (LH; 16.4%; n = 98) and High drinking/High symptoms (HH; 27.5%; n = 164). The HH group was characterized by more delinquent peer associations, and rates of community violence were higher among the high symptom groups. The HH group had the highest severe violence perpetration and victimization rates across time points; the LH group had similar violence rates to the LM and NM groups and the LN group had the lowest violence rates across time. Conclusions: Among drug-using youth, alcohol use interventions could benefit from a focus on peer influences, and those with a joint focus on violence involvement may be improved via inclusion of content related to mental health and community violence exposure.